Accuracy of Adult Children’s Perceptions of Mothers’ Caregiver Preferences - Suitor, J Jill (Gerontologist, 2019)
BACKGROUND AND OBJECTIVES: Most older mothers have strong preferences regarding which offspring will serve as their future caregivers, and violation of these preferences has been found to have consequences for mothers’ psychological well-being. However, no study has examined the accuracy of adult children’s perceptions of their mothers’ caregiver preferences. In this article, we compare mothers’ stated preferences for particular caregivers with their adult children’s perceptions of their mothers’ preferences. RESEARCH DESIGN AND METHODS: Data were collected from 675 adult children and their mothers nested within 285 families as part of the Within-Family Differences Study. RESULTS: Only 44.6% of adult children accurately reported their mothers’ preferences for particular offspring as caregivers. Consistent with our hypotheses, accuracy was higher when mothers and children shared values regarding filial piety, and lower when children were parents, had poor health, and lived further away. Surprisingly, primary caregivers were substantially less likely to accurately report mothers’ caregiver preferences than were noncaregivers. This counterintuitive pattern can be explained by the finding that most mothers were cared for by children whom they did not prefer and may have therefore been reluctant to share their preferences with those caregivers. DISCUSSION AND IMPLICATIONS: Given the negative psychological consequences for mothers whose caregiver preferences are violated, the high level of inaccuracy found among adult children has important implications when mothers face serious health events. These findings underscore the need for intervention efforts to encourage practitioners and clinicians to collect information directly from mothers regarding preferences for particular offspring as caregivers.